Data from: A comparative morphometric study of sensory capacity in geometrid moths - Javoiš, Juhan; Davis, Robert B.; Tammaru, Toomas (Dryad, 2019)
Diet breadth and the degree of capital breeding have been established as
major determinants of species-specific ecology of herbivorous insects. The
relationship of these variables with sensory capacity, although allowing
an array of hypotheses, has remained poorly studied, let alone in
phylogenetically explicit multi-species comparisons. We contribute to
filling this gap in a study of 60 species of geometrid moths (Lepidoptera:
Geometridae), using adult head measures (eye size, antennal length and
shape, forehead width) as indices of sensory capacity. When controlled for
body size, eyes of capital breeding species were found to be smaller, and
female antennae shorter, than in income breeders. Feathery (vs simple
filiform) male antennae were more frequently present in the capital
breeders and in larger species. Regarding diet breadth, generalist species
were found to have relatively wider male foreheads than specialists. The
results suggest that (a) breeding strategy rather than diet breadth
predicts sensory capacity in geometrids, (b) capital breeding (vs income
breeding) is related to low sensory capacity in females, and (c) in
contrast, males of the capital breeding species have evolved towards
elevated olfactory capacity.
Data used in Javoiš et al (Journal of Evolutionary Biology)Data set
containing species used in the study of sensory capacity of geometrid
moths. Data collected from lab, photo-based measurements and literature
sources.javoiš_et_al_data.xls
Keywords: plumose antennae; cognitive capacity; Geometridae; pectinate antennae; phylogenetic generalised least squares; olfaction; Visual; Host specificity; niche breadth